Decreased circulating transforming growth factor-beta (TGF-β) and kidney TGF-β immunoreactivity predict renal disease in cats with naturally occurring chronic kidney disease - Piyarungsri, Kakanang; Chuammitri, Phongsakorn; Pringproa, Kidsadagon; Pila, Pattiya; Srivorakul, Saralee; Sornpet, Benjaporn; Pusoonthornthum, Rosama (Journal of feline medicine and surgery, 2023)
Objectives The aim of the present study was to compare the circulating transforming growth factor-beta (TGF-β) of clinically normal age-matched and naturally occurring chronic kidney disease (CKD) cats and to determine the correlation between the TGF-β expression and histopathological changes in cats with CKD. Methods A total of 11 clinically normal age-matched and 27 cats with naturally occurring CKD were included in this study. Circulating TGF-β was quantified by immunoassays. Kaplan–Meier analysis was used to calculate the association between survival time and the concentration of circulating TGF-β. A general linear model was used to compare the circulating TGF-β between groups. Immunohistochemical analyses revealed TGF-β expression in renal tissues from cats with CKD that died during the study (n = 7) and in available archived renal tissue specimens taken at necropsy from cats that had previous CKD with renal lesions (n = 10). Correlations of the TGF-β expression and clinical parameters (n = 7) and histopathological changes (n = 17) were analysed using Spearman’s rank correlation. Results The median survival time of cats with a lower concentration of circulating TGF-β was shorter than that of cats with a higher concentration. The area under the curve of circulating TGF-β for predicting CKD was 0.781, indicating good differentiation. The study indicated a significant difference in circulating TGF-β concentrations between clinically normal cats and those with CKD and demonstrated that TGF-β expression is correlated with tubular atrophy. Conclusions and relevance The study findings suggest that decreased serum TGF-β and tubular atrophy with TGF-β immunoreactivity may be significant in cats with CKD.